2009 International Joint Conference on Neural Networks 2009
DOI: 10.1109/ijcnn.2009.5178661
|View full text |Cite
|
Sign up to set email alerts
|

A Computational study of pre-synaptic re-uptake of dopamine on phosphorylation of DARPP-32

Abstract: The activity of mid brain dopamine (DA) neurons resembles the reward prediction error signal of the Temporal Difference (TD) model. Dopamine acting at Dl receptor activates adenylate cyclase through the coupling of Dl receptors with G s / o l f • The complex of adenylate cyclase activates and increases the intracellular levels of cAMP and thereby stim ulating cAMP dependent protein kinase and increasing the state of phosphorylation of DARPP-32 (dopamine and cyclic AMPregulated phosphoprotein, M, = 32,000). DAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Our study produces the results that match well with the experimental and simulated data such as phosphorylation of DARPP-32 (Wanjerkhede and Bapi 2009), time course of phosphorylation of CaMKII, PKA activity, and percentage of open state of NMDAR (Wanjerkhede 2006). Ahn et al (2007) have investigated the mechanism of Ca 2+ -dependent regulation of Thr-75 by PP2A, and showed that PR72 (or B or PPP2R3A) regulatory subunit of PP2A is highly expressed in striatum.…”
Section: Model Robustnesssupporting
confidence: 74%
“…Our study produces the results that match well with the experimental and simulated data such as phosphorylation of DARPP-32 (Wanjerkhede and Bapi 2009), time course of phosphorylation of CaMKII, PKA activity, and percentage of open state of NMDAR (Wanjerkhede 2006). Ahn et al (2007) have investigated the mechanism of Ca 2+ -dependent regulation of Thr-75 by PP2A, and showed that PR72 (or B or PPP2R3A) regulatory subunit of PP2A is highly expressed in striatum.…”
Section: Model Robustnesssupporting
confidence: 74%